Pemberlakuan Pidana Mati Menurut Hukum Pidana Nasional Dan Hukum Islam - Haryadi, Tobi (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
The death penalty in Indonesia is regulated by Law No. 2 of the 1964 National Program for Standard Formulation, which stipulates execution by firing squad, although it is often criticized as a form of cruel treatment. Initially, Article 11 of the Criminal Code regulated execution by hanging, but this was later changed to execution by firing squad for civilians. Meanwhile, in Islamic criminal law, the death penalty varies, including stoning and qishash, depending on the type of criminal offense committed.